2003
DOI: 10.1046/j.1369-7625.2003.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical messages in the media – barriers and solutions to improving medical journalism

Abstract: Context Medical issues are widely reported in the mass media. These reports influence the general public, policy makers and health-care professionals. This information should be valid, but is often criticized for being speculative, inaccurate and misleading. An understanding of the obstacles medical reporters meet in their work can guide strategies for improving the informative value of medical journalism.Objective To investigate constraints on improving the informative value of medical reports in the mass med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
118
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 18 publications
(34 reference statements)
3
118
0
4
Order By: Relevance
“…20 Celebrities can successfully raise awareness about a health issue, but it is a greater challenge for health journalists to ensure accurate understanding. 22 This is difficult when the issue involves an understanding of risk and probabilities as is true of the genetic information that Angelina Jolie communicated. In this regard, approximately one-third of our respondents (31.7%) incorrectly predicted how many times a coin would come up heads in 1,000 coin flips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Celebrities can successfully raise awareness about a health issue, but it is a greater challenge for health journalists to ensure accurate understanding. 22 This is difficult when the issue involves an understanding of risk and probabilities as is true of the genetic information that Angelina Jolie communicated. In this regard, approximately one-third of our respondents (31.7%) incorrectly predicted how many times a coin would come up heads in 1,000 coin flips.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that clinicians seek ways to reach the most vulnerable and high-risk populations with clear and useful information. 4,10,22 Preparing for inevitable future events similar to the Angelina Jolie's announcement involves transforming heightened public awareness into heightened public understanding and appropriate use of medical resources.…”
Section: Discussionmentioning
confidence: 99%
“…For health journalism in particular, remedies such as research appraisal training for journalists have been suggested to improve the accuracy and completeness of research coverage (e.g., Oxman et al 1993;Larsson et al 2003;Moynihan 2003;Schwartz and Woloshin 2004). Health news coverage can be inaccurate or incomplete, with important consequences for health and healthcare at times (e.g., Cassels et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Health researchers have also established that news coverage of therapeutic risks and benefits can be inaccurate or incomplete, raising concerns that media can encourage inappropriate changes in behaviour and services utilization (Moynihan et al 2000;Cassels et al 2003). Consequently, many health researchers suggest interventions to make news coverage less "sensational" and more "evidence-based," for example, by training journalists in the critical appraisal of research evidence (e.g., Oxman et al 1993;Larsson et al 2003;Moynihan 2003;Schwartz and Woloshin 2004).…”
Section: Résumémentioning
confidence: 99%
“…A tal fin se usaron diferentes métodos de medición para determinados temas específicos relacionados con salud; sólo un estudio utilizó un instrumento genérico correctamente desarrollado y validado que permitió medir la calidad de varios tópicos (8). Por otro lado, se han identificado algunos factores que podrían actuar como barreras para mejorar la calidad (9).…”
unclassified